Who Manages the Pressure? Gaps, Challenges and Policy Needs in Inpatient Hypertension Care - Mohammad Mujtaba Khokhar, Hassan Sarfraz khan, Saad Saeed Virk, Waleed Ibrahim, Zafar Aleem Suchal, Azra Mahmud (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Background: Elevated blood pressure (BP) during hospitalization affects 50–70% of adults, yet formal international guidance on its management remains absent. Increases in BP may reflect true hypertension, transient physiological stress, or inaccuracies in measurement. This study assessed how hypertension is managed in clinically stable hospitalized patients in a tertiary care setting. Methods: We conducted a prospective, observational, cross-sectional study at Shalamar Hospital, Lahore, Pakistan from November 2024 to March 2025. Adult inpatients (≥18 years) with a prior or new diagnosis of hypertension were enrolled consecutively. Data were collected at a single time point using structured questionnaires and medical record review. Statistical analysis was performed using JMP Version 13 (SAS), p<0.05 considered significant. Results: Of the 151 hypertensive patients (mean age 58.2 ± 12.8 years; 68.9% female), 90.7% had pre-existing hypertension, and 83% were on treatment. Common comorbidities included type 2 diabetes (81.9%) and chronic kidney disease (13.8%). Half of the patients had BP <140/90, mmHg during hospitalization, but adverse events included hypertensive urgency (5.3%), creatinine rise (23%), and myocardial infarction (2.6%). Inpatient prescribing showed a significant decline in angiotensin receptor blocker (44.4% vs. 36.4%, p<0.01) and beta-blocker (19.9% vs. 13.2%, p<0.05) use, and a rise in calcium channel blocker (38.4% vs. 47.7%, p<0.01) and diuretic (7.3% vs. 11%, p=0.06) use. Despite this, 25% had uncontrolled BP at discharge; 70% had no documented outpatient follow-up, and only 19% were referred to specialist care. Conclusion: Managing hypertension in hospitalized patients remains a clinical challenge, particularly in the presence of multimorbidity, acute illness, and evolving treatment priorities. The absence of formal guidelines, limited prescribing oversight, and lack of structured discharge planning contribute to suboptimal control and follow-up. Our findings highlight the need for clear institutional protocols, better integration of inpatient and outpatient care, and enhanced clinical support to ensure safe, consistent, and evidence-based management of hypertension during hospitalization.